The Relationship between Body Weight and Fasting Blood Glucose Levels in Students of the Faculty of Medicine, Tadulako University, Class of 2022 - Tri Setyawati; Rabiatul Adawiyah; Haya Khumairah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Introduction: Obesity and excess body weight are predisposing factors to insulin resistance which can cause an increase in blood sugar levels resulting in type 2 diabetes mellitus.Objective: To determine the relationship between body weight and fasting blood glucose levels in students of the Faculty of Medicine Untad Batch 2022Methods: This type of research is analytic observational using a cross sectional research design. Total population of 159 people. The sampling technique used total sampling and obtained a total sample of 139 which met the inclusion and exclusion criteria. Data were obtained by measuring body mass index and taking peripheral blood using a glucometer. Then the data obtained were analyzed using the Spearman test.Results: The results of the analysis showed that there was no significant relationship between body weight and fasting blood glucose levels in Tadulako University Medical Faculty students class of 2022 with a p value of 0.39. The results of the analysis on the relationship between BMI and fasting blood glucose levels in 2022 Faculty of Medicine students showed no significant relationship with a p value of 0.24.Conclusion: It can be concluded from the study that there is no significant relationship between body weight and fasting blood glucose levels in Tadulako University Medical Faculty students class of 2022. This is because the majority of the sample has normal weight.